A traveling wave ultrasonic motor with a metal/polymer-matrix material compound stator. (18th December 2017) - Li, Jinbang; Liu, Shuo; Zhou, Ningning; Yu, Aibing; Cui, Yuguo; Chen, Pengfei
Abstract: This study proposes a traveling wave ultrasonic motor with a metal/polymer-matrix material compound stator. The stator is composed of a metal ring and polymer-matrix teeth. The resonance frequency of the stator with different structural dimensions was analyzed by the finite element method. From the results, the structure parameters of the metal ring were obtained. The effects of the density and elastic modulus of the tooth material on the resonance frequency were also investigated. A viscoelastic contact model was built to explore the contact state between the compound stator and rotor. Considering the density, elastic modulus and tribological properties, the tooth material was prepared by a molding process. The load–torque and efficiency–torque characteristics of the motor with different tooth thicknesses were measured under different preloads using a preload controlled ultrasonic motor test device. The maximum no-load speed of the motor was about 85 r min −1 with a tooth thickness of 3 mm and a preload of 100 N, the maximum stall torque of the motor was about 0.5 N · m with a tooth thickness of 4 mm and a preload of 125 N, and a maximum efficiency of about 5.5% occurred with a tooth thickness of 4 mm, a preload of 100 N and a torque of 0.3 N · m. The main merits of the proposed ultrasonic motor are low cost, light weight, high processing efficiency and long life.